THE EVALUATION OF CURRICULUM 2013 POLICY AT SDN 03 KUALA MANDOR B KUBURAYA REGENCY - Trifornia Ernawati NIM. E1011151087; H Sugito *; Sitorus * (PublikA, Jurnal Ilmu Administrasi Negara, 2019)
Tujuan penelitian ini adalah untuk mengkaji dan mengevaluasi implementasi kebijakan kurikulum 2013 di SDN 03 Kuala Mandor B , Kabupaten Kubu Raya. Penelitian ini di dasari pada fenomena permasalahan yang terjadi yaitu rendahnya kemampuan guru dalam menerapkan prinsip-prinsip kurikulum 2013 dan minimnya sarana dan prasarana sekolah. Di dalam penelitian ini peneliti menggunakan jenis penelitian Deskritif ekploratif dengan menggunakan metode Kualtitatif. Subjek dalam penelitian yakni Ketua Pengawas Tingkat Sekolah Dasar Kecamatan Kuala Mandor B, Kepala Sekolah SDN 03 Kuala Mandor B, Guru kelas 1 dan 4, Komite Sekolah, Orang tua murid , Siswa kelas 1 dan 4. Hasil dari penelitian ini yaitu Implementasi kebijakan kurikulum 2013 di SDN 03 Kuala Mandor B sudah di terapkan namun belum berjalan dengan optimal karna masih terdapat kendala yaitu Guru masih belum memahami prinsip-prinsip kurikulum 2013 pada proses pembelajaran,masih kurangnya sarana dan prasarana sekolah, kurangnya pengawasan dari Pengawas Tingkat Sekolah Dasar Kecamatan Kuala Mandor B, rendahnya minat dan kemampuan siswa dalam membaca dan belajar dan kurangnya perhatian orang tua siswa terhadap pendidikan anak. Rekomendasi penelitian ini adalah Guru-guru dapat memahami dan menerapkan 14 prinsip-prinsip kurikulum 2013 dalam proses kegiatan belajar mengajar di sekolah, di harapkan Pengawas Tingkat Sekolah Dasar Kuala Mandor B dan Kepala Sekolah dapat lebih serius dalam melakukan pengawasan yang lebih intensif untuk melihat kinerja guru dan kondisi sekolah dalam proses implementasi kebijakan kurikulum 2013 di sekolah. Kata Kunci : Evaluasi kebijakan, Kurikulum 2013, Sekolah Dasar. THE EVALUATION OF CURRICULUM 2013 POLICY AT SDN 03 KUALA MANDOR B KUBURAYA REGENCY By : Trifornia Ernawati 1* NIM. E1011151087 Dr.H.Sugito,M.Si 2 , R.L.Sitorus,S.E,M.Si 2 *Email: trifornia.ernawati11@gmail.com 1. Student of Public Administration Program Study of Social and Political Sciences Faculty of Tanjungpura University Pontianak. 2. Lecturer of Public Administration Program Study of Social and Political Sciences Faculty of Tanjungpura University Pontianak. ABSTRACT The purpose of this research was to study and evaluate the implementation of curriculum 2013 policy at SDN 03 Kuala Mandor B, Kubu Raya Regency. This research was based on the phenomenon of problems that occur such as the low ability of teachers to apply the principles of curriculum 2013 as well as the lack of school facilities and infrastructures. In this study, the researcher used a type of exploratory descriptive research by using a qualitative method. The subjects in this study were the chief suppervisor at the Primary School level of the Kuala Mandor B sub-district, the school principal of the SDN 03 Kuala Mandor B, the teachers of grade 1 and 4, school committees, parents of students, and the students of 1st and 4st grades. The results of this study indicate that the implementation of policy of curriculum 2013 at SDN 03 Kuala Mndor B has been carried out. However,it has not run optimally due to some obstacles such as teachers who still do not understand the principles of curriculum 2013 in terms of learning process implementation. Moreover, there are still lack school facilities and infrastructure,lack of supervision from the primary school level supervisors of Kuala Mandor B sub-district, low interest and ability of students in reading and learning, not to mention, lack of parents’ attention to children’s education. The recommendation generated from this study is that teachers need to understand how to apply the 14 principles of curriculum 2013 regardding the process of teaching and learning activities in school. Thus, both supervisors and school principals at Kuala Mandor B Elementary School level are expected to be more serious in cunducting more intensive supervision in order to see teachers’ performance and school conditions regarding the process of implementing the curiculum 2013 policy in schools. Keywords : policy evaluation, curriculum 2013, Elementary Scholl.